High-speed vibration-milling-promoted synthesis of symmetrical frameworks containing two or three pyrrole units - Leonardi, Marco; Villacampa, Mercedes; Menéndez, J. Carlos (Beilstein Journal of Organic Chemistry, 2017)
The pseudo-five-component reaction between β-dicarbonyl compounds (2 molecules), diamines and α-iodoketones (2 molecules), prepared in situ from aryl ketones, was performed efficiently under mechanochemical conditions involving high-speed vibration milling with a single zirconium oxide ball. This reaction afforded symmetrical frameworks containing two pyrrole or fused pyrrole units joined by a spacer, which are of interest in the exploration of chemical space for drug discovery purposes. The method was also extended to the synthesis of one compound containing three identical pyrrole fragments via a pseudo-seven-component reaction. Access to compounds having a double bond in their spacer chain was achieved by a different approach involving the homodimerization of 1-allyl- or 1-homoallylpyrroles by application of cross-metathesis chemistry.
Keywords: diversity-oriented synthesis; mechanochemistry; multicomponent reactions; pyrroles; solvent-free synthesis

(untitled) - Lv, Z.; Chu, Y.; Wang, Y. (HIV/AIDS, 2015)

(untitled) - Staderini, M.; Legname, G.; Bolognesi, M. L.; Menéndez, J. C. (Curr. Top. Med. Chem., 2013)

(untitled) - De Petrocellis, L.; Arroyo, F. J.; Orlando, P.; Schiano Moriello, A.; Vitale, R. M.; Amodeo, P.; Sánchez, A.; Roncero, C.; Bianchini, G.; Martín, M. A.; López-Alvarado, P.; Menéndez, J. C. (J. Med. Chem., 2016)

(untitled) - Stolle, A.; Szuppa, T.; Leonhardt, S. E. S.; Ondruschka, B. (Chem. Soc. Rev., 2011)

(untitled) - James, S. L.; Adams, C. J.; Bolm, C.; Braga, D.; Collier, P.; Friščić, T.; Grepioni, F.; Harris, K. D. M.; Hyett, G.; Jones, W.; Krebs, A.; Mack, J.; et al. (Chem. Soc. Rev., 2012)

(untitled) - Bowmaker, G. A. (Chem. Commun., 2013)

(untitled) - Wang, G.-W. (Chem. Soc. Rev., 2013)

(untitled) - Claramunt, R. M.; López, C.; Sanz, D.; Elguero, J. (Adv. Heterocycl. Chem., 2014)

Comprehensive Organic Synthesis - Hernández, J. G.; Avila-Ortiz, C. G.; Juaristi, E. (Useful Chemical Activation Alternatives in Solvent-Free Organic Reactions, 2014)

(untitled) - Hernández, J. G.; Friščić, T. (Tetrahedron Lett., 2015)

(untitled) - Do, J.-L.; Friščić, T. (ACS Cent. Sci., 2017)

(untitled) - Hernández, J. G.; Bolm, C. (J. Org. Chem., 2017)

Mechanochemical Organic Synthesis - Davor, M.; Štrukil, V. (Elsevier, 2016)

(untitled) - Estévez, V.; Villacampa, M.; Menéndez, J. C. (Chem. Commun., 2013)

(untitled) - Estévez, V.; Sridharan, V.; Sabaté, S.; Villacampa, M.; Menéndez, J. C. (Asian J. Org. Chem., 2016)

(untitled) - Zhao, H.; Dietrich, J. (Expert Opin. Drug Discovery, 2015)

(untitled) - Sridharan, V.; Menéndez, J. C. (Chem. Rev., 2010)

(untitled) - Mills, J. S.; Showell, G. A. (Expert Opin. Invest. Drugs, 2004)

(untitled) - Gately, S.; West, R. (Drug Dev. Res., 2007)

(untitled) - Franz, A. K.; Wilson, S. O. (J. Med. Chem., 2013)